CR-submanifolds of a locally conformal Kaehler space form - M. Hasan Shahid (International Journal of Mathematics and Mathematical Sciences)
(Bejancu [1,2]) The purpose of this paper is to continue the study of CR-submanifolds, and in particular of those of a locally conformal Kaehler space form (Matsumoto [3]). Some results on the holomorphic sectional curvature, D-totally geodesic, D1-totally geodesic and D1-minimal CR-submanifolds of locally conformal Kaehler (1.c.k.)-space from M¯(c) are obtained. We have also discussed Ricci curvature as well as scalar curvature of CR-submanifolds of M¯(c).